The ANFIS as a Prediction Method of Efficiency of PV Cells - Beken, Murat; Kayisli, Korhan; Eyecioglu, Onder; Yagci, Ozlem; Icelli, Orhan (IEEE, 2018)
In this study, the efficiency and output voltage of the photo-voltaic (PV) cells which is doped with Boric acid (113803) at different concentrations ((0, 0.625, 1.25, 2.50, 3.75 and 5.00 mg / ml) has been predicted using Adaptive Neural Fuzzy Inference System (ANF1S) as artificial intelligence methods. We have shown that the results obtained with ANFIS are in harmony with experimental studies. Therefore, the ANFIS method can be handled as a practical tool to predict output voltage of the PV cells under different conditions.
Keywords: Solar cell; Artificial Intelligence; ANFIS; PEDOT; PSS; Boric acid; Science & Technology - Other Topics; Energy & Fuels; Engineering